THE SUSTAINABLE DEVELOPMENT INDICATORS FOR THE ENERGY SECTOR - Margina, Oleg; Irina, Popa (Economics of Agriculture, 2012)
In Romania are used all the sources of energy offered by the nature to sustain the energy sector. The increasing need of energy along with the growth of the population creates a difficulty in responding to the big quantity that is required. The proportions in which the energy sources compose the electricity production are different, the composition includes in majority fossil fuels used as prime matter for energy production and less, different on countries and growing in the recent period, the renewable sources. The evaluation of the sector is very important and relevant for choosing the future sources of energy. Hence comes the need of strengthen the indicators system. For Romania the energy sector is at the beginning of its reorientation but there is seen a possibility for sustainable energy production and consumption in the future of the Romanian sector because of the European restrictions and their guidance.